Leveraging of sulfur anions in photoinduced molecular transformations - Li, Haoyu (2022)
This perspective describes recent advances in the use of sulfur anions to promote molecular transformations under irradiation with visible light. The topics are classified by the following reaction modes performed by the key sulfur anions: (1) C-S coupling via electron donor-acceptor (EDA) interactions, (2) photoinduced molecular transformation via sulfur anion EDA catalysis, (3) sulfur anions as photoredox and hydrogen atom transfer (HAT) catalysts, and 4) dithiocarbamate and xanthate as nucleophilic catalysts for photoinduced radical cascade reactions.